Águas que Produzem Gente como Nós: desenvolvimento e mundivivências de Mayombe – Cabinda (Angola) - João Milando (Cadernos de Estudos Africanos)
African societies comprise a multiplicity of social actors who are still invisible to «development operators». In the case of the bayombe, in Cabinda, Angola, among these «invisible» actors appear spiritual entities that «populate» the local waters. The article deals with these social entities and the way they condition social representations and practices of local populations. Through the observation of these «invisible» actors, the text explores the ways of living of these populations, confronting them implicitly with some underlying logics of the developmentalist paradigm.